The Pedagogic Architecture of MOOC: A Research Project on Educational Courses in Spanish - Fernández-Díaz, Elia; Rodríguez-Hoyos, Carlos; Calvo Salvador, Adelina (International Review of Research in Open and Distributed Learning, 2017)
This study has been carried out within the context of the ECO European Project (E-learning, Communication Open-Data: Massive Mobile, Ubiquitous, and Open Learning) which is being financed by the European Union over four years (2014-17). It analyses the pedagogic architecture of MOOC on pedagogic/educational subjects in Spanish over one academic year (September 2015-June 2016). The analysis focuses on five major dimensions from a qualitative perspective: subjects and the promoting institution, methodology, resources, type of videos, and evaluation. The results demonstrate the hegemony of subjects linked to the Society of Knowledge, such as the widespread use of traditional methodology based on video lessons (the “talking head” model). Communication tools are clearly underused and evaluation based on the use of questionnaires is dominant. The findings show the need for further research into MOOC based on a pedagogic approach such as the one adopted here.